2016
DOI: 10.1038/jp.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Enteral feeding during indomethacin treatment for patent ductus arteriosus: association with gastrointestinal outcomes

Abstract: This large retrospective study did not identify any association between enteral feed volumes during indomethacin treatment or preemptive reduction in enteral feeds and subsequent incidence of adverse gastrointestinal outcomes in preterm neonates. Preemptive reduction in enteral feed volume was associated with longer time to reach full enteral feeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…More recently, similar findings have been reported by Louis et al [65], who retrospectively investigated the prevalence of NEC stage ≥ 2a [61], feeding intolerance, defined as at least two consecutive gastric aspirates of >50% of previous feed volume or any aspirate containing bile or blood, time to enteral intakes of 120 and 160 mL/kg/day, and length of parenteral nutrition in relation to enteral feeding intakes at the time of indomethacin therapy in preterm neonates with PDA. Based on their enteral feed volume exposure during treatment, the enrolled infants were stratified into the following groups: NPO (n = 229); intake ≤ 60 mL/kg/day (n = 142); intake > 60 mL/kg/day (n = 44).…”
Section: Association Between Pda Feeding Practices and Gi Outcomessupporting
confidence: 73%
“…More recently, similar findings have been reported by Louis et al [65], who retrospectively investigated the prevalence of NEC stage ≥ 2a [61], feeding intolerance, defined as at least two consecutive gastric aspirates of >50% of previous feed volume or any aspirate containing bile or blood, time to enteral intakes of 120 and 160 mL/kg/day, and length of parenteral nutrition in relation to enteral feeding intakes at the time of indomethacin therapy in preterm neonates with PDA. Based on their enteral feed volume exposure during treatment, the enrolled infants were stratified into the following groups: NPO (n = 229); intake ≤ 60 mL/kg/day (n = 142); intake > 60 mL/kg/day (n = 44).…”
Section: Association Between Pda Feeding Practices and Gi Outcomessupporting
confidence: 73%
“…Indomethacin is widely used to treat patent ductus arteriosus in human neonates ( 27 , 28 ). Previous studies have demonstrated that a partial ligation of the arterial duct in utero was able to induce PPHN in sheep ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Allow feedings with patent ductus arteriosus, even if receiving Indomethacin [55,56] Develop and implement unit-specific standardized feeding guidelines, including threshold dosing of medication (e.g., vasopressors, etc.) to determine if enteral feedings can be initiated and/or continued [28] One of the most significant barriers to initiating and advancing enteral feeding in preterm infants is clinician fear of NEC.…”
Section: Hemodynamic Instabilitymentioning
confidence: 99%